Formulation and evaluation of fast dissolving tablets of amlodipine besylate by using Fenugreek seed mucilage and Ocimum basilicum gum - Sukhavasi, Sudheshnababu; Kishore, V. Sai (International Current Pharmaceutical Journal, 2012)
Fast dissolving/disintegrating tablets have received ever-increasing demand during the last decade, and the field has became a rapidly growing area in the pharmaceutical area. Particularly the fast dissolving drug delivery systems formulated with natural polymers have more demand because natural materials like gums and mucilages have been extensively used in the field of drug delivery for their easy availability, ease administration, non toxicity, non irritant nature etc. The main aim of the present study was to formulate the fast dissolving tablets of amlodipine besylate tablets using Fenugreek seed mucilage and Ocimum basilicum gum as a natural superdisintegrating agents to achieve quick onset of action, is to increase the water uptake with in shortest wetting time and there by decrease the disintegration time of the tablets by simple and cost effective direct compression technique. Pre-compression parameters like angle of repose and post-compression parameters like wetting time, water absorption ratio, in-vitro disintegration and in-vitro dispersion time were studied. The hardness, friability and drug content of all the formulations were found to be within the limits. The best formulations FFGK5 & FOB5 have shown good disintegration time, hardness and friability. The best formulations were also found to be stable. Optimized formulation was subjected to stability studies as per ICH guidelines and it insignificant change in hardness, disintegration time and in vitro drug release. DOI: http://dx.doi.org/10.3329/icpj.v1i9.11614 International Current Pharmaceutical Journal 2012, 1(9): 243-249